2012
DOI: 10.7324/japs.2012.2830
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Topical Formulation Containing S. Lutea Extract: Stability, In Vitro Studies and Cutaneous Permeation

Abstract: Flavonoids have been widely incorporated into cosmetic and dermatological formulations, affording benefits such as antioxidant action, improved skin tone and fewer lines and wrinkles. Brazil has a huge biodiversity, with one of the richest flora in the world, and existing studies justify the quest for greater research efforts in this area. The cajazeira (Spondias lutea L.), a plant of the Anacardiaceae family from tropical America, is widely disseminated in Brazil. This plant was chosen because of the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Flavonoids are a class of phenolic compounds. Therefore, flavonoid content will be lower than phenolic content, and this supports the result obtained for both TFC and TPC of the KMO formulation and the control formulation, as the KMO formulation and the control formulation had phenolic content higher than total flavonoid content [24]. Correlations between antioxidant activity, DPPH inhibition and TFC would be lower than those of TPC, as the aluminium chloride method is specific to detect flavones and flavonols only.…”
Section: Total Flavonoid Content (Tfc)supporting
confidence: 80%
See 1 more Smart Citation
“…Flavonoids are a class of phenolic compounds. Therefore, flavonoid content will be lower than phenolic content, and this supports the result obtained for both TFC and TPC of the KMO formulation and the control formulation, as the KMO formulation and the control formulation had phenolic content higher than total flavonoid content [24]. Correlations between antioxidant activity, DPPH inhibition and TFC would be lower than those of TPC, as the aluminium chloride method is specific to detect flavones and flavonols only.…”
Section: Total Flavonoid Content (Tfc)supporting
confidence: 80%
“…Higher total phenolic content indicates higher antioxidant activity [21][22]. Flavonoids are secondary metabolites from plants that exhibit antioxidant, anti-inflammatory, and antibacteria activities [23][24]. The compounds contain high phenolic antioxidants such as kojic acid, vitamin C and niacinamide, often used in cosmetic products as a defense against free radicals [25].…”
mentioning
confidence: 99%
“…Although rutin permeated the skin, the compound was also found in the stratum corneum (3.27 ± 1.92 μg/mL) by tape stripping test and in higher concentration in the retention test (114.68 ± 8.70 μg/mL). Studies performed by Chuang et al [75] and Isaac et al [76] showed release and deposit of flavonoids when incorporated in topical formulations. Moreover, Chuang et al [75] determined that the viable skin, specially the stratum corneum, could be a barrier delaying flavonoid permeation by enhancing compound deposition.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important phytoconstituents in medicinal plants are polyphenols, in particular flavonoids. Flavonoids are a class of plant secondary metabolites with great cosmetic potential due to their excellent antioxidant, anti-inflammatory and antibacterial activities [ 54 ]. In addition, flavonoids have been suggested in treating the signs of aging by different mechanisms including their antioxidant properties by free radical scavenging and metal chelation with metalloenzymes providing antiprotease activities [ 55 ], sunscreen effect, and restoration of UV-induced DNA damage [ 56 ].…”
Section: Discussionmentioning
confidence: 99%